2018
DOI: 10.4102/ac.v18i1.604
|View full text |Cite
|
Sign up to set email alerts
|

Communication channels in the host community market adopted by Chinese immigrant entrepreneurs

Abstract: Orientation: There is a growing prevalence of entrepreneurial activity by immigrant entrepreneurs in different sectors of various economies across the world. Immigrant entrepreneurs seek to identify opportunities to grow and sustain their businesses in hostile business markets. Immigrant entrepreneurs use an array of channels of communication to gain insight of the opportunities in the market.Research purpose: The study sought to investigate the communication channels used by Chinese immigrant entrepreneurs to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The profile of the participants as well as the rate of adoption and the level of awareness data were analysed quantitatively using Excel spreadsheet. The five principles of research: credibility, dependability, transferability, conformability and research ethics were observed and maintained all the time, to ensure quality (Ndoro et al, 2018). In terms of ethical considerations, all the respondents were recruited on a voluntary basis.…”
Section: Discussionmentioning
confidence: 99%
“…The profile of the participants as well as the rate of adoption and the level of awareness data were analysed quantitatively using Excel spreadsheet. The five principles of research: credibility, dependability, transferability, conformability and research ethics were observed and maintained all the time, to ensure quality (Ndoro et al, 2018). In terms of ethical considerations, all the respondents were recruited on a voluntary basis.…”
Section: Discussionmentioning
confidence: 99%